Toxic wavelength of blue light changes as insects grow. - Kazuki Shibuya; Shun Onodera; Masatoshi Hori (PLoS ONE)
Short-wavelength visible light (blue light: 400-500 nm) has lethal effects on various insects, such as fruit flies, mosquitoes, and flour beetles. However, the most toxic wavelengths of blue light might differ across developmental stages. Here, we investigate how the toxicity of blue light changes with the developmental stages of an insect by irradiating Drosophila melanogaster with different wavelengths of blue light. Specifically, the lethal effect on eggs increased at shorter light wavelengths (i.e., toward 405 nm). In contrast, wavelengths from 405 to 466 nm had similar lethal effects on larvae. A wavelength of 466 nm had the strongest lethal effect on pupae; however, mortality declined as pupae grew. A wavelength of 417 nm was the most harmful to adults at low photon flux density, while 466 nm was the most harmful to adults at high photon flux density. These findings suggest that, as the morphology of D. melanogaster changes with growth, the most harmful wavelength also changes. In addition, our results indicated that reactive oxygen species influence the lethal effect of blue light. Our findings show that blue light irradiation could be used as an effective pest control method by adjusting the wavelength to target specific developmental stages.